Healing in Herero culture and Namibian African independent churches - Kgatla, Selaelo Thias ca. 20./21. Jh. (HTS teologiese studies, 2015)
The current phenomenon of Namibian African Independent Churches (NAICs) draws attention from various people in civil society in Namibia. Although the ministries of NAICs are engaged with activities which are unusual for Christian churches, such as healing the people, fighting against evil spirits and power, performing certain rituals, prophesying and leading the worship services with African Traditional Religion (ATR) as a frame of reference in 21st century, they do have a very big influence on various aspects of society in Namibia, which cannot be ignored. This is because those activities are familiar to the everyday lives of Africans and in touch with their culture. With regards to this, this article focuses on the causes of integration or harmony between the Herero culture and the NAICs.